Interplay among Oxidative Stress, Methylglyoxal Pathway and S-Glutathionylation - Lidia de Bari; Andrea Scirè; Cristina Minnelli; Laura Cianfruglia; Miklos Peter Kalapos; Tatiana Armeni (MDPI AG, 2020)
Reactive oxygen species (ROS) are produced constantly inside the cells as a consequence of nutrient catabolism. The balance between ROS production and elimination allows to maintain cell redox homeostasis and biological functions, avoiding the occurrence of oxidative distress causing irreversible oxidative damages. A fundamental player in this fine balance is reduced glutathione (GSH), required for the scavenging of ROS as well as of the reactive 2-oxoaldehydes methylglyoxal (MGO). MGO is a cytotoxic compound formed constitutively as byproduct of nutrient catabolism, and in particular of glycolysis, detoxified in a GSH-dependent manner by the glyoxalase pathway consisting in glyoxalase I and glyoxalase II reactions. A physiological increase in ROS production (oxidative eustress, OxeS) is promptly signaled by the decrease of cellular GSH/GSSG ratio which can induce the reversible S-glutathionylation of key proteins aimed at restoring the redox balance. An increase in MGO level also occurs under oxidative stress (OxS) conditions probably due to several events among which the decrease in GSH level and/or the bottleneck of glycolysis caused by the reversible S-glutathionylation and inhibition of glyceraldehyde-3-phosphate dehydrogenase. In the present review, it is shown how MGO can play a role as a stress signaling molecule in response to OxeS, contributing to the coordination of cell metabolism with gene expression by the glycation of specific proteins. Moreover, it is highlighted how the products of MGO metabolism, S-D-lactoylglutathione (SLG) and D-lactate, which can be taken up and metabolized by mitochondria, could play important roles in cell response to OxS, contributing to cytosol-mitochondria crosstalk, cytosolic and mitochondrial GSH pools, energy production, and the restoration of the GSH/GSSG ratio. The role for SLG and glyoxalase II in the regulation of protein function through S-glutathionylation under OxS conditions is also discussed. Overall, the data reported here stress the need for further studies aimed at understanding what role the evolutionary-conserved MGO formation and metabolism can play in cell signaling and response to OxS conditions, the aberration of which may importantly contribute to the pathogenesis of diseases associated to elevated OxS.